Unraveling the Influence of the Electrolyte on the Polarization Resistance of Nanostructured La0.6Sr0.4Co0.2Fe0.8O3-δ Cathodes - Zamudio-García, Javier; Caizán-Juanarena, Leire; Porras-Vázquez, José Manuel; Ramírez-Losilla, Enrique; Marrero-López, David (IOAP-MPDI, 2022)
Large variations in the polarization resistance of La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) cathodes are reported in the literature, which are usually related to different preparation methods, sintering temperatures, and resulting microstructures. However, the influence of the electrolyte on the electrochemical activity and the rate-limiting steps of LSCF remains unclear. In this work, LSCF nanostructured electrodes with identical microstructure are prepared by spray-pyrolysis deposition onto different electrolytes: Zr0.84Y0.16O1.92 (YSZ), Ce0.9Gd0.1O1.95 (CGO), La0.9Sr0.1Ga0.8Mg0.2O2.85 (LSGM), and Bi1.5Y0.5O3-δ (BYO). The ionic conductivity of the electrolyte has a great influence on the electrochemical performance of LSCF due to the improved oxide ion transport at the electrode/electrolyte interface, as well as the extended ionic conduction paths for the electrochemical reactions on the electrode surface. In this way, the polarization resistance of LSCF decreases as the ionic conductivity of the electrolyte increases in the following order: YSZ > LSGM > CGO > BYO, with values ranging from 0.21 Ω cm2 for YSZ to 0.058 Ω cm2 for BYO at 700 °C. In addition, we demonstrate by distribution of relaxation times and equivalent circuit models that the same rate-limiting steps for the ORR occur regardless of the electrolyte. Furthermore, the influence of the current collector material on the electrochemical performance of LSCF electrodes is also analyzed
Keywords: Electrólitos; Nanostructured materials; SOFC; Cathode; Electrolyte; Spray-pyrolysis